Nucleophosmin deposition during mRNA 3' end processing influences poly(A) tail length and mRNA export - Sagawa, Fumihiko, author; Wilusz, Jeffrey, advisor; Wilusz, Carol J., advisor; Reddy, Anireddy S. N., committee member; Thamm, Douglas, committee member (Colorado State University. Libraries, 2011)
During polyadenylation the multi-functional protein nucleophosmin is deposited onto all cellular mRNAs analyzed. Premature termination of poly(A) tail synthesis using cordycepin abrogates deposition of the protein onto the mRNA, indicating natural termination of poly(A) addition is required for nucleophosmin binding. Nucleophosmin appears to be a bona fide member of the complex involved in 3' end processing as it is directly associated with the AAUAAA-binding CPSF-160 protein and can be co-immunoprecipitated with other polyadenylation factors. Furthermore, reduction in the levels of nucleophosmin results in hyperadenylation of mRNAs, consistent with alterations in poly(A) tail chain termination. Finally, knock down of nucleophosmin results in retention of poly(A)+ RNAs in the cell nucleus, indicating that nucleophosmin binding influences mRNA export. Collectively these data suggest that nucleophosmin plays an important role in poly(A) tail length determination and helps network 3' end processing with other aspects of nuclear mRNA maturation.
Keywords: mRNA export; Nucleophosmin; polyadenylation; poly(A) tail; RNA